Confounders or intermediate variables? Testing mechanisms for the relationship between depression and smoking in a longitudinal cohort study. (March 2015) - Chaiton, Michael; Cohen, Joanna E.; Rehm, Jürgen; Abdulle, Mohamed; O'Loughlin, Jennifer
Abstract: Introduction: The relationship between the onset of smoking and the onset of depression among adolescents has been well document, but the mechanisms underlying the relationship are unclear. This paper uses an empirical method to assess potential intermediate variables in the pathway between changes in depressive symptoms and cigarette smoking in a longitudinal cohort of adolescents. Methods: 837 participants from a cohort in Montreal, Canada who had not smoked and did not have elevated depressive symptoms at baseline were followed for five years from 1999 to 2003. The role of a set of 15 variables previously identified in the literature as potential confounders were systematically evaluated as predictors of exposure and outcome, for attenuation of the association by more than 10%, and for intra-individual change in the variable after onset of exposure. Results: The magnitude of the association between smoking and depressive symptoms was fully attenuated after adjustment for all variables included indiscriminately. A concept map was developed detailing the empirical associations between the variables within this data set. Stress, worry about weight, and worry about parents were identified as intermediate variables for both smoking predicting depressive symptoms and depressive symptoms predicting smoking. Cox regressions with appropriate confounders maintained statistical significance. Conclusion: Cigarette smoking is associated with higher depressive symptoms prior to and after inclusion of empirical confounders. Inclusion of intermediate variables in multivariable models can lead to the erroneous conclusion that there is no association between smoking and depression. Highlights: The relationship of depressive symptoms and smoking is a complex one. Care must be taken to differentiate between intermediate variables and confounders. Pathways between depressive symptoms and smoking varied by the direction of effect. Stress and friend smoking were important intermediate variables.